2013
DOI: 10.1097/01.ewx.0000432183.50644.f6
|View full text |Cite
|
Sign up to set email alerts
|

Androgenetic alopecia

Abstract: Androgenetic alopecia (AGA) and female pattern hair loss are highly prevalent in our society. In recent years, many strides have been made in understanding the epidemiology and the pathophysiology of this disease; yet, there are few truly effective treatments. In this paper, we review some of the recent research on the epidemiology, pathophysiology, and treatment of AGA. Further studies on genetics, mechanisms of disease, and novel therapies will likely lead to more efficacious treatment and improved outcomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 124 publications
0
2
0
Order By: Relevance
“…Unfortunately, with age and undefined factors, the incidence of baldness or alopecia is growing in the worldwide. 29) This dermatological disease relates to important medical and psychosocial matters, because the hair loss affects individual emotions and social perceptions. 30) Therefore, it is important to investigate to understand the molecular mechanisms of hair loss and develop candidates to prevent it.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, with age and undefined factors, the incidence of baldness or alopecia is growing in the worldwide. 29) This dermatological disease relates to important medical and psychosocial matters, because the hair loss affects individual emotions and social perceptions. 30) Therefore, it is important to investigate to understand the molecular mechanisms of hair loss and develop candidates to prevent it.…”
Section: Discussionmentioning
confidence: 99%
“…In South African adults, the incidence of AGA was 14.6% in men and 3.5% in women, although it was a younger population than in other studies. Numerous studies conducted on Asian communities have revealed usually lower rates than those of White groups, with an all-age prevalence of about 20% for men and 5-6% for women [8].…”
Section: Epidemiology A-incidencementioning
confidence: 97%
“…The AGA onset usually appears between the age of 30-40 years and affects approximately 50% of men by the age of 50 years and 50% of women by the age of 60 years [2]. In all populations, predominance increase with age, however thinning might begin as early as puberty [8]. By the age of 70, less than 15% of males have little to no baldness [9].…”
Section: B Agementioning
confidence: 99%
“… 3 AGA's impact on appearance and psychosocial experiences can affect the quality of life (QOL). 4 Despite numerous models exploring AGA pathogenesis, there are only 2 FDA approved treatments (finasteride and minoxidil). 5 …”
Section: Introductionmentioning
confidence: 99%